Kajian Laboratorium Penggunaan Pasir Pantai Panjang Bengkulu Sebagai Bahan Tambahan Aggregat Halus Pada Hotmix AC-WC (Asphalt Concrete-Wearing Course) - Tugiman Tugiman; Yulanda Putri (MAJALAH TEKNIK SIMES, 2020)
Abstract In an effort to increase the strength of pavement structures in addition to the use of hot asphalt mixture with new specifications, the selection of material types used is very important. In addition to asphalt, coarse aggregates and fine aggregates, the filler is one component in the mixture that has a large role to Marshall properties which is also a mixed performance against the traffic load. The implementation of this pilot work aims to compare mixed / stirring results using only stone ash and mixture/stirring using a beach-type additive in the AC-WC composition. Implementation of this pilot work using the Marshall method, where the Marshall test is obtained results in the form of components Marshall, namely stability, flow, Void In Total Mix (VITM), Void Filled with Asphalt (VFA) and then can be calculated Marshall Its quotiety. The last test is a Marshall immersion test or Immersion test. The result of comparison between the use of fine aggregate using only rock ash and the addition of coastal sand to the properties of Marshall AC-WC (Asphalt Concrete-Wearing Course) is based on marshall characteristic values indicating that the use of sand in asphalt concrete mixture produces a stable AC- WC layer against Change in shape (smooth and solid), but has no durability to the effects of traffic load reps and is bleeding, and is not flexible enough to break easily and break.